Mastering DynamoDB : master the intricacies of the NoSQL database DynamoDB to take advantage of its fast performance and seamless scalability /: master the intricacies of the NoSQL database DynamoDB to take advantage of its fast performance and seamless scalability. (2014) - Unknown
No abstract available